Asymmetric synthesis of 1H-pyrrol-3(2H)-ones from 2, 3-diketoesters by combination of aldol condensation with benzilic acid rearrangement. Issue 1 (26th October 2015) - Sha, Qiang; Arman, Hadi; Doyle, Michael P.
Abstract : A highly efficient two-step asymmetric synthesis of 1 H -pyrrol-3(2 H )-one derivatives from conveniently accessed 2, 3-diketoesters. Aldol products are obtained with up to 89/11 d.r. and 99% ee. Benzilic acid rearrangement produces 1 H -pyrrol-3(2 H )-ones in good yields without loss of enantioselectivity. Abstract : An efficient two-step protocol for the asymmetric synthesis of 1 H -pyrrol-3(2 H )-one derivatives in 99% ee from conveniently accessed 2, 3-diketoesters has been developed.